Rich forests, rich people? Sustainable finance and its links to forests. (15th January 2023) - Begemann, A.; Dolriis, C.; Winkel, G.
Abstract: Investment products labelled as sustainable, as well as regulations on sustainable finance, such as the EU taxonomy for sustainable activities, are on the rise globally. While some of these products and regulations include forests and forestry, the forest–sustainable finance nexus is largely unexplored in academic research. This paper systematically analyses the emerging expert debate spanning across the financial and forest sectors. We conducted 51 in-depth qualitative interviews with experts from financial institutions, timberland and impact investors, international organizations, civil society organizations and academia. We chose mainly experts from Europe, as one of the regions spearheading the topic globally. Based on these, we identify five main narratives on the nexus between sustainable finance and forests. These narratives are strikingly different regarding such dimensions as emphasis on risks versus opportunities, preference for public versus private governance and investments, as well as on the sustainability of forest-related investments per se . While financial sector experts are mainly concerned about financial risks, and only partially about deforestation risks, forest sector experts with financial expertise promote investment opportunities either for the asset class, or to increase private investment in tropical forests. In contrast, some experts from both the forest and financial sectors explicitly exclude forests as investable assets for the private sector, seeing them instead as pure public goods. We conclude with underlining the importance of more cross-sectoral dialogue, but also research, to both critically assess and advance the role of sustainable finance policy and practice in supporting forest conservation, restoration, and sustainable management. Highlights: We analyse the link between sustainable finance and forests based on 51 expert interviews. Five distinct narratives can be distinguished, differing strongly regarding several dimensions. Differences include varying risk/opportunity, private/public governance, and forest/sustainability emphases. Financial sector experts prefer mitigating financial risks, and partially deforestation ones. Forest sector experts aim to increase investment opportunities.